2021
DOI: 10.1136/gutjnl-2021-325317
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to corticosteroids in pregnancy is associated with adverse perinatal outcomes among infants of mothers with inflammatory bowel disease: results from the PIANO registry

Abstract: ObjectiveActive inflammatory bowel disease (IBD) during pregnancy may require the use of corticosteroids. The aim of this study was to investigate the impact of in utero corticosteroid exposure on adverse pregnancy outcomes, congenital malformations, infections and neurocognitive development among offspring of mothers with IBD.DesignUsing the prospective Pregnancy in Inflammatory Bowel Disease and Neonatal Outcomes registry, data were collected at each trimester, delivery; and in the 12 months post partum. Biv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 23 publications
1
21
0
2
Order By: Relevance
“…The PIANO registry demonstrated that corticosteroid use was significantly associated with increased risks of preterm birth, LBW and neonatal intensive care unit admission. This registry data also revealed that corticosteroid use in second and/or third trimesters was associated with serious infant infection requiring hospitalization, which is consistent with our finding of neonatal death with corticosteroids in metaregression analysis 9 . In our study, the majority of the included patients were organ transplantation recipients and low‐dose prednisone was dominantly prescribed in addition to CNIs to prevent graft rejection, although not all studies showed the type of corticosteroids and its dose.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The PIANO registry demonstrated that corticosteroid use was significantly associated with increased risks of preterm birth, LBW and neonatal intensive care unit admission. This registry data also revealed that corticosteroid use in second and/or third trimesters was associated with serious infant infection requiring hospitalization, which is consistent with our finding of neonatal death with corticosteroids in metaregression analysis 9 . In our study, the majority of the included patients were organ transplantation recipients and low‐dose prednisone was dominantly prescribed in addition to CNIs to prevent graft rejection, although not all studies showed the type of corticosteroids and its dose.…”
Section: Discussionsupporting
confidence: 90%
“…A recent prospective Pregnancy in IBD and Neonatal Outcomes (PIANO) registry 8 reported that biologic, thiopurine or combination therapy exposure during pregnancy was not associated with increased adverse maternal or foetal outcomes. However, this registry recently revealed that corticosteroid use was significantly associated with increased risks of preterm birth, LBW and neonatal intensive care unit admission 9 . While previous investigations suggest that CNI‐treated patients may have increased risks of neonatal prematurity or gestational hypertensive disorders, more studies evaluating the safety of CNIs in particular are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Due to small numbers of individual inflammatory risk factors and the frequent overlap of episodes experienced in the preterm group, we created binary outcome measures based on combinations of inflammatory risk factors or conditions experienced, combining infants that experienced three or more morbidities into a single group, resulting in four possible levels for the risk score of 0, 1, 2, or 3 + alongside a term control reference (0 inflammatory episodes). Results are presented firstly unadjusted (model H1), then adjusted for gestational age at birth, infant sex and birthweight z-score (model H2), and then adjusted for gestational age at birth, infant sex and birthweight z-score as well as administration of MgSO4 and corticosteroids in pregnancy (model H3), given these have been identified as potential confounders of the relationship between inflammation and health outcomes in previous studies (83)(84)(85). Results are presented as odds ratios (OR) and 95% confidence intervals (CI) for categorical outcome measures.…”
Section: Multiple Inflammatory Hits and Dnam Crpmentioning
confidence: 99%
“…American guidelines differ somewhat, suggesting only babies exposed to biologics in third trimester need to avoid live vaccines for the first 6 months 3. There is increased use of biologics throughout pregnancy including the third trimester given the results of large registries, including the Pregnancy Inflammatory bowel disease And Neonatal Outcomes (PIANO) registry, which support the safety of antitumour necrosis factor medications and highlight the risks of active disease in pregnancy 4…”
mentioning
confidence: 99%